Overview of Knowledge of Pregnant Women About the Dangers of Covid-19 During Pregnancy - Ainun N N; Magdalena Limbong; Erna Kasim; Nurhayati Nurhayati; Ricky Zainuddin (Newinera Publisher, 2023)
Corona Virus Disease 2019 (COVID-19) is a disease that attacks the respiratory tract, and one of the groups vulnerable to exposure to the virus is pregnant women due to physiological changes in pregnant women. Case studies conducted with a qualitative method are descriptive, the population used is pregnant women who are less knowledgeable about the dangers of Covid-19 during pregnancy in the form of purposive sampling. The data taken are primary data and calculations of questionnaire results using the guttman scale. Based on a case study that has been carried out on 2 respondents who are in accordance with the inclusion criteria in knowing the Picture of Knowledge of Pregnant Women about the danger signs of Covid-19 during Pregnancy in the Maccini Sawah Puakesmas Work Area which was carried out for 4 days, the case study obtained by the level of knowledge of pregnant women was categorized as good with a value of 95%-100% after being given knowledge with education. The Level of Knowledge of Pregnant Women Regarding the Danger Signs of Covid-19 during Pregnancy is greatly influenced by the level of knowledge and the environment, the lack of information also greatly affects the level of knowledge of pregnant women about the Dangers of Covid-19 during pregnancy. Pregnant women need to understand and know the dangers of Covid-19 to pregnancy, so it is very necessary to increase knowledge to avoid the risk of being infected with Covid-19.